Fake news as a disruptive textual production: blows in social fields - Bentes, Anna Christina (2023)
In this article, we intend to present a textual-discursive approach to fake news, postulating that they are communicative practices structured through large-scale textual production, a production conceived and incorporated both in the journalistic field and in the political field. At the same time as textual-discursive characteristics of the symbolic production of these fields are explored, fake news contributes to its deterioration, by building suspicion about the legitimacy of institutions in general, of state agents and, especially in the case of Brazil, also about electoral and health procedures. At the same time as they seek symbolic deterioration, especially in journalistic and political fields, the social agents responsible for this large-scale textual production try to establish the legitimacy of new actors and other trajectories in these social fields, especially through disintermediation, establishing an environment of life-or-death dispute in the social space, which seems to be at its peak in Brazil. In this sense, large-scale textual production is an important instrument both to maintain this dispute environment and to give continuity to the processes of insertion, legitimation and delegitimization of the various actors in various social fields.